French Learning Based on Malay Ecology for High School Students in Medan City - Irwandy; M. Oky Fardian Gafari; Malan Lubis; Muhammad Hafidz Assalam (Britain International for Academic Research (BIAR) Publisher, 2022)
Learning French in high school carries an introduction to French culture as a form of cultural acculturation. Learning French is not only about learning the language, but also about culture. Even so, in learning French texts, students still have to negotiate with the foreign culture they are studying. There needs to be an adaptation of the French language into the ecological culture of the learner. So far, French teaching materials have not been sufficient to accommodate the ecological culture of students. Learning French doesn't have to be French. In the cultural context that surrounds students, students must also be able to collaborate between the Basic Competencies that must be achieved with the ecological relevance of using French. Therefore, it is necessary to present teaching materials for French Language Subjects based on Malay Ecology for high school students in the city of Medan. Malay is a culturally strong base in the city of Medan, so that the teaching materials also represent students' needs to survive in the ecological culture that surrounds them. This article presents the results of research that produces products in the form of teaching materials for French language subjects based on Malay ecology for high school students in Medan City. The aims of the research were 1) to produce teaching materials for French language subject based on Malay ecology for high school students in Medan City, 2) to measure the validity of teaching materials for French language subject based on Malay ecology for high school students in Medan City. This research uses the development method with the ADDIE model (Analysis, Design, Develop, Implementation, Evaluation). Validity test involves material and design experts. Based on the validity test, the results obtained were that the teaching materials obtained an average score of 88.75% by two validators in the very feasible category. The follow-up validity test was applied to high school students and teachers in Medan City with an average acquisition of 88.05% in the very decent category. This validation test uses a questionnaire technique to collect data on the feasibility of teaching materials based on the assessment of high school students and teachers in Medan City. Research products will be implemented in schools that are partners in the research.